AI PLATFORMS AND DIGITAL PEDAGOGY IN FOREIGN LANGUAGE EDUCATION - Qodirova Mohichehra Zafar qizi; Xolmatova Maxbubaxon Axmadjon qizi (International Journal of Literature and Language Studies, 2026)
Annotation. This article examines the role of Artificial Intelligence (AI) platforms and digital pedagogy in foreign language education. It explores how AI-powered tools such as machine translation, conversational agents, and language learning applications support learners in developing their language skills. The study highlights the advantages of these technologies, including personalized learning, increased motivation, and improved access to educational resources. At the same time, it discusses the challenges associated with their use, such as overreliance on technology, lack of real human interaction, and technical limitations. The article also analyzes popular AI platforms and their features in enhancing language learning. Overall, the paper emphasizes the importance of balancing technology with traditional teaching methods to achieve effective learning outcomes.